Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan di Bengkel Motor - Glenn Kevin Daniel Silitonga; Ditta Febrieta; Yomima Viena (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine the effect of service quality on customer satisfaction at motorcycle repair workshops. The research employs a quantitative method with a causal approach. The population consists of motorcycle workshop customers in the Mustika Sari area, with a sample of 96 respondents determined using the Cochran formula. Data were collected through questionnaires using a 4-point Likert scale. Data analysis included descriptive statistical analysis, assumption tests (normality, linearity, and homogeneity), Pearson correlation analysis, and simple linear regression analysis. The results show that service quality has a significant effect on customer satisfaction, with a Pearson correlation coefficient of 0.875 and a significance value of p < 0.001. The coefficient of determination (R²) of 0.766 indicates that 76.6% of the variance in customer satisfaction can be explained by service quality. These findings indicate that the better the service quality provided, the higher the level of customer satisfaction. Therefore, continuous improvement in service quality, including aspects of tangibles, reliability, responsiveness, assurance, and empathy, is necessary to enhance customer satisfaction and ensure the sustainability of motorcycle repair workshop businesses.